2000
DOI: 10.1046/j.1365-246x.2000.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of the propagation path and the arrest of fluid-filled fractures in the Earth

Abstract: Summary We use a boundary element method to study the growth and quasi‐static propagation of fluid‐filled fractures in regions with inhomogeneous and deviatoric stresses. The wholesale migration of fractures due to their opening at one end and closing at the other can be simulated when using a finite fluid mass contained in a fracture and considering fluid compression or expansion with changing fracture volume; these fractures are driven by stress gradients and by the density differences between the fluid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
167
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(176 citation statements)
references
References 43 publications
(57 reference statements)
9
167
0
Order By: Relevance
“…We simply assume that the dikes propagate orthogonal to σ3. Numerical models of dike propagation (Dahm, 2000;Maccaferri et al, 2011) and analog experiments (Watanabe et al, 2002) revealed that dike trajectories depend on the competition between dike overpressure and the external stresses (i.e., loading or unloading). High-overpressure dikes are expected to propagate straight, insensitive to spatial inhomogeneities of the stress field.…”
Section: Unloading Pressure Vs Dike Overpressure Control On the Erupmentioning
confidence: 99%
“…We simply assume that the dikes propagate orthogonal to σ3. Numerical models of dike propagation (Dahm, 2000;Maccaferri et al, 2011) and analog experiments (Watanabe et al, 2002) revealed that dike trajectories depend on the competition between dike overpressure and the external stresses (i.e., loading or unloading). High-overpressure dikes are expected to propagate straight, insensitive to spatial inhomogeneities of the stress field.…”
Section: Unloading Pressure Vs Dike Overpressure Control On the Erupmentioning
confidence: 99%
“…[61] Geophysical observations [Battaglia et al, 2005], numerical [Dahm, 2000] and analog models [Rivalta and Dahm, 2005] indicate that dikes grow upward or laterally from the source region. Thus it is unlikely that the stress changes induced by the shallow dike would promote the injection of magma downward to the deeper dike.…”
Section: Eruption Modelmentioning
confidence: 99%
“…Assuming a closed system, a dyke will tend to be emplaced such that it minimizes the total potential energy 15,16,17 , Θ T , equal to:…”
mentioning
confidence: 99%